The Effect of Ambiguity Awareness on Second Language Learners’ Prosodic Disambiguation - Zhang, Yuanyuan; Ding, Hongwei (Frontiers in Psychology, 2020)
Three tasks were reported to examine the effect of ambiguity awareness on Chinese-speaking English learners’ use of prosody in resolving prepositional phrase-attachment ambiguity. In the first (Task 1) and second (Task 2) tasks, listeners were not informed of the syntactic ambiguity. In the third task (Task 3), listeners were given the specific information about syntactic ambiguity. The analysis of the overall accuracy rate showed that before receiving specific information about syntactic ambiguity, learners did not detect the ambiguity within the structure and tended to interpret the sentence in a ‘good-enough’ heuristic to reduce the computational burden. After being aware of the syntactic ambiguity, they could use prosodic cues to resolve the ambiguity. However, the finding that learners reversed their parsing bias from VP-attachment towards NP-attachment indicated their difficulty in integrating prosodic information to syntactic structure efficiently. The analysis of individual accuracy rate demonstrated learners’ individual variations in using prosodic cues. The result suggests that learners’ failure to use prosodic cues may be attributed to a lack of ambiguity awareness and difficulty in information integration, rather than their low sensitivity to prosodic cues.